Freeboard and Trim Measurement: a Case Study of Landing Craft Tank Conversion to Ship Power Plan - Suardi Suardi; Wira Setiawan; Samsu Dlukha Nurcholiq; Alamsyah Alamsyah; Andi Mursid Nugraha Arifuddin; Amalia Ika Wulandari; Muhammad Uswah Pawara (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
In this research, the ship power plan which is the result of a conversion from a landing craft tank is designed to meet the electricity needs in areas affected by a disaster or electricity crisis. So far, the government has chartered a similar ship from Turkey which is used to meet electricity needs in Indonesian areas which have been affected by the disaster and electricity crisis. This ship is modified to carry an electric generator which can later be sent to areas that need it. Two main focuses are the goal of this research, the first is to find the value of the freeboard and the second is the trim of the ship after the redesign. To achieve this goal, in this study a numerical calculation method was used to calculate the freeboard and trim values according to applicable standards. The results of the analysis show that the freeboard value is still safe, with the actual freeboard value being greater than the required freeboard (0.8 m > 0.44 m). For ship trim, the bow trim condition is obtained with a smaller LCG-LCB difference than the 0.05% LPP value (0.912 < 0.923). By looking at the results of these measurements, the condition of the ship's freeboard and trim is still in a fairly good category even though it has been converted from a landing craft tank to a ship power plant. This study can provide a reference for ship design before converting the actual ship so that it can carry out trim and freeboard tests to prevent build failures.